Forecast-guided simulation for optimizing cargo handling personnel requirements - Gunawan Gunawan; Miltiades Salvador Da Costa Sarmento; Okto Dinaryanto; Marni Astuti; Bangga Dirgantara Adiputra; Riani Nurdin; Yasrin Zabidi; Uyuunul Mauidzoh (OPSI, 2026)
The increase in the number of cargo handling at the Ahmad Yani Airport Domestic Cargo Terminal has reached 217.18% from 2009 to 2019, but decreased by 47% in 2020 due to the COVID-19 pandemic. It will affect the service in cargo handling, especially the number of personnel and facilities. This research was conducted to determine the optimal number of Cargo handling personnel at a logistics company in 2024. The forecasting methods used are Linear Moving Average, Double Exponential Smoothing Brown's, and Simple Linear Regression, where these methods will be compared to see which method has the smallest error value. Then a cargo handling simulation model will be created for this company in 2024 to find out the optimal number of Cargo handling personnel at the logistics company uses ARENA Simulation Software. The results show that in 2024 with the simple linear regression method (which has the smallest error) around 7,816,594.9 kg of Cargo is predicted as incoming Cargo, and around 7,847,581.01 kg of Cargo is predicted as outgoing Cargo in that year at the logistics company. And from the simulation model, it is found that to optimize the number of cargo handling personnel, the number of additional personnel required is 1 Aviation Security, Dispatcher, and Transporter.